A comparative study of the structure, magnetic properties of Terbium and Erbium doped Yttrium Iron Garnet thin films - Shaiboub, Ramadan; Aldbea, Ftema (Sharwes Scientific Journal, 2025)
رThe structure and magnetic properties of (Tb0.4Y2.6Fe5O12) and (Er0.4Y2.6Fe5O12) thin films were fabricated onto quartz substrate by a sol–gel method followed by spin coating process. Heat treatment of the films was processed at 900 oC in air for 2-3hrs. The crystalline structures and magnetic properties of samples were investigated by X- ray diffraction (XRD), the field emission scanning electron microscope (FESEM) and vibrating sample magnetometer (VSM). The XRD patterns of the (Tb0.4Y2.6Fe5O12) and (Er0.4Y2.6Fe5O12) films were consistent with single phase garnet structure. FE-SEM micrographs of films reveal that the particles were highly agglomerated. The grain size for the (Tb0.4Y2.6Fe5O12) film was about 50 nm, while for (Er0.4Y2.6Fe5O12) film found about 68 nm and the average thicknesses ranged from 180 - 245 nm. The magnetic measurements at room temperature show that the saturation magnetization (Ms) and the coercivity (Hc) of (Tb0.4Y2.6Fe5O12) film is about (67 emu/cm3) and 14 Oe, while for (Er0.4Y2.6Fe5O12) film it’s about                                                          (51 emu/cm3) and 37 Oe respectively.